MORPHOLOGY OF PLEUROPNEUMONIA-LIKE ORGANISMS AND BACTERIAL L FORMS GROWN IN LIQUID MEDIA - Weibull, C. (1963)
Weibull, C. (Central Bacteriological Laboratory of Stockholm City, Stockholm, Sweden) and Britt-Marie Lundin. Morphology of pleuropneumonia-like organisms and bacterial L forms grown in liquid media. J. Bacteriol. 85:440–445. 1963.—Cells of Mycoplasma hominis, M. laidlawii, and two tissue-culture strains of pleuropneumonia-like organisms (PPLO) moving freely in liquid medium were photographed with an electronic flash as the light source. The photomicrographs thus obtained demonstrated that, in young cultures of high viability, the cells of these organisms were mainly filamentous or, in the case of M. laidlawii, coccoid. In old cultures of the same organisms containing predominantly nonviable cells, granular and vesicular elements were found. By the use of the same photographic technique, liquid cultures of a stable Proteus L form were studied. Although no filaments of uniform thickness were found, there were spherical bodies and some threadlike material connected with the spheres. When samples of PPLO cultures containing filamentous forms were transferred to agar blocks, the filaments were converted to more or less spherical bodies. This conversion could be prevented by fixing the PPLO with formaldehyde. The morphology of Proteus L forms was not noticeably altered by fixation with this reagent.